El éxito en la escasez. La defensa de Cartagena de Indias en 1741 (2016)
ABSTRACT: This article analyses the various factors involved in the defence of Cartagena de Indias in 1741, and the relationship between them. The main feature was a lack of defensive resources. The article looks at naval elements, fortifications, supplies and strategic decisions that were directly related to the English attack against this Spanish city, culminating in a resounding success for Spain.